EL-HIFDZI (Muroja’ah dan Talaqqil Qur’an): Solusi untuk Mempermudah Setor Hafalan dan Muroja’ah Online Berbasis Aplikasi Android - Salmah Islamiati; Uswah Mujahidah Rasuna Said; Agus Umar Dani; Arief Fiddienika (Indonesian Journal of Social and Educational Studies, 2020)
Muroja'ah is memorizing and repeating the memorization of the Al-qur’an that students do to Ustaz. As for Talaqqi in terms of language, it is taken from words, namely learning face to face with Ustaz. These two methods are direct methods that are often used by schools with the Tahfizul Qur'an program in Indonesia. Entering the industrial revolution 4.0, a method of memorization and memory deposit is required that can be done remotely and online. Therefore, this article aims to produce a system design for memorizing and depositing verses of the Al-Qur'an equipped with an android application-based error correction feature. The user will be asked to record a voice and the application will translate the voice into writing. Then the writing will be matched with the Al-Qur’an database and display the results of a review of the system if there is a verse error. The output that will be produced is an animated video that describes the application virtually. This animated video is designed through several stages starting from making the StoryBoard application, interface design, compiling a video script, creating animated characters, and making animated videos. The literature used to support the implementation of this stage is literature taken from books, journals, and the internet as well as other sources.